2015
DOI: 10.1590/1983-084x/11_090
|View full text |Cite
|
Sign up to set email alerts
|

Estudo farmacobotânico de partes aéreas vegetativas de aroeira-vermelha (Schinus terebinthifolius Raddi, Anacardiaceae)

Abstract: RESUMO:Schinus terebinthifolius Raddi (Anacardiaceae), conhecida como aroeira-vermelha é uma espécie nativa do Brasil, perenifólia e pioneira, sendo muito utilizada para combater diversas doenças, pois apresenta, entre outras, propriedades anti-inflamatórias e cicatrizantes. O objetivo desta pesquisa foi realizar um estudo morfoanatômico do caule e da folha de S. terebinthifolius, descrevendo a organização dos tecidos e suas possíveis variações. As análises macro e microscópicas foram realizadas com material s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
1
8
0
12
Order By: Relevance
“…According Metcalfe & Chalk ,37 the presence of crystalline inclusions in plant leaves can be associated with an adaptive mechanism for greater capture of light and optimize the photosynthesis rate. In studies conducted by Azevedo and contributors, 49 characteristics similar to petiolule anatomy of S. mombin were found in the petiole of Schinus terebinthifolius (Anacardiaceae) as vascular bundles with collateral arrangement and the presence of secretory cavities well developed, generally associated to the phloem. The lumen of the ducts located in the phloem is also oval in cross section in young stems of Anacardium occidentale.…”
Section: Lithraea Molleoidesmentioning
confidence: 79%
“…According Metcalfe & Chalk ,37 the presence of crystalline inclusions in plant leaves can be associated with an adaptive mechanism for greater capture of light and optimize the photosynthesis rate. In studies conducted by Azevedo and contributors, 49 characteristics similar to petiolule anatomy of S. mombin were found in the petiole of Schinus terebinthifolius (Anacardiaceae) as vascular bundles with collateral arrangement and the presence of secretory cavities well developed, generally associated to the phloem. The lumen of the ducts located in the phloem is also oval in cross section in young stems of Anacardium occidentale.…”
Section: Lithraea Molleoidesmentioning
confidence: 79%
“…For aroeira, results showed that levels of shading between 20 and 40% did not affect SLA. Aroeira are pioneer species, therefore, they are expected to tolerate full sunlight treatment (Azevedo, Quirino, & Bruno, 2015). Accordingly, plants subjected to 90% shade produced leaves with the greatest SLA values.…”
Section: Resultsmentioning
confidence: 99%
“…The present study provided a better understanding of the anatomy of the species and its behavior in relation to different luminous intensities, both in relation to leaf temperature (AZEVEDO, et al, 2015). Escolheu-se esta espécie para a pesquisa por ser nativa da região, e seus múltiplos usos ampliam a relevância da pesquisa para a comunidade em geral.…”
Section: Resultsunclassified